Insecticidal activity of the medicinal plant, Alstonia boonei De Wild, against Sesamia calamistis Hampson - Oigiangbe, O.N.; Igbinosa, I.B.; Tamo, Manuele (2007)
The bioactivity of the aqueous extracts of the leaf and stem bark of the medicinal plant, Alstonia boonei De Wild (Apocyanaceae), against the pink stalk borer, Sesamia calamistis Hampson (Lepidoptera: Noctuidae) was studied in a laboratory bioassay. The extracts were incorporated into artificial diet at a rate of 0.0% (control), 1.0%, 2.5%, 5.0%, and 10.0% (w/w). Both extracts significantly (P<0.01) reduced larval survival and weight in a dose dependent manner. The concentrations that killed 50% of the larvae (LC50) for the stem bark extract were 2.8% and 2.1% at 10 and 20 DAI (days after introduction), respectively, while those for the leaves extract were 5.6% and 3.5%. The weights of the larvae also varied significantly (P<0.05) between the treatments in a dose dependent manner. We conclude that both leaf and stem bark extracts of A. boonei are toxic, used as growth inhibitors to S. calamistis larvae, and hold good promise for use as alternative crop protectants against S. calamistis.